2020
DOI: 10.1039/c9nr10334a
|View full text |Cite
|
Sign up to set email alerts
|

Local mucosal immunization of self-assembled nanofibers elicits robust antitumor effects in an orthotopic model of mouse genital tumors

Abstract: In this study, we proposed that local mucosal immunization of nanofibers via the intravaginal route represented a promising vaccination strategy for the treatment of genital tumor lesions such as cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Recently, Ryan and co-authors demonstrate that STAT1 is an essential mediator of the antitumor response through the inhibition of myeloid derived suppressor cell accumulation and promotion of T-cell mediated immune responses in murine HPV− head and neck squamous cell carcinoma [103]. Many other studies were conducted with the aim to investigate antitumor effects in HPV+ murine models, so Li et al recently published that their candidate vaccine against HPV16E7 significantly reduced Treg and MDSCs infiltration in mouse genital tumors [104,105]. Given the creation of a new immunocompetent mouse model of HPV16+ head and neck squamous cell carcinoma [106], this promising vaccination strategy should be considered and tested for the treatment of HPV+ oropharyngeal SCC.…”
Section: Myeloid Cellsmentioning
confidence: 99%
“…Recently, Ryan and co-authors demonstrate that STAT1 is an essential mediator of the antitumor response through the inhibition of myeloid derived suppressor cell accumulation and promotion of T-cell mediated immune responses in murine HPV− head and neck squamous cell carcinoma [103]. Many other studies were conducted with the aim to investigate antitumor effects in HPV+ murine models, so Li et al recently published that their candidate vaccine against HPV16E7 significantly reduced Treg and MDSCs infiltration in mouse genital tumors [104,105]. Given the creation of a new immunocompetent mouse model of HPV16+ head and neck squamous cell carcinoma [106], this promising vaccination strategy should be considered and tested for the treatment of HPV+ oropharyngeal SCC.…”
Section: Myeloid Cellsmentioning
confidence: 99%
“…Intravaginal administration is another mucosal immunization route for controlling genital cancer and was demonstrated to be more effective than the subcutaneous route at suppressing orthotopic genital tumor growth. 28 Lee et al demonstrated that the intravaginal administration, but not subcutaneous immunization, of a vaccine containing HPV peptides and flagellin as an adjuvant could suppress orthotopic genital tumor growth and promote the long-term survival of tumor-bearing mice. 29 However, also using an orthotopic genital tumor model, Decrausaz et al reported that subcutaneous immunization of a therapeutic HPV peptide vaccine that included two adjuvants elicited more robust cell-mediated responses compared with mucosal vaccination and promoted the regression of tumors in the genital mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In a later study, this same vaccine formulation was found to be more effective at suppressing tumor growth when delivered via mucosal immunization, specifically intravaginally, compared to subcutaneously. [ 73 ] Another potential immunotherapy was developed against tumor necrosis factor (TNF) mediated inflammation by covalent modification of Q11 with B‐cell epitope TNF 4‐23 , or CD4+ T cell eptiopes PADRE (aKXVAAWTLKAa, X = cyclohexylalnine) and Vaccinia I1L 7‐21 . [ 74 ] Coassemblies of TNFQ11 with either PADREQ11 or VACQ11 protected mice from TNF‐mediated inflammation, proving the potential of Q11 for various immunotherapies.…”
Section: Applicationsmentioning
confidence: 99%